Pengaruh Proses Pack Carburizing Baja AISI 4340 Terhadap Peningkatan Kekerasan dan Ketahanan Aus - Azmy, Ilham; Masruri, Deden; Rahardyanto, Rivaldy; Suyitno, Suyitno (Fakultas Teknik UMSU, 2022)
The AISI 4340 steel is widely used in severe load such as shaft, crankshafts, and connecting rods in automobile and machinery industry which required to capable maintain high mechanical strength and toughness. Since this material is very important for mechanical and engineering usage, the long wear solicitation must be required. However, it requires to high surface hardness to achieve longer lifetime and less damage. To tackle this problem, the research proposes novel experimental method of pack carburizing process on AISI 4340 steel to construct carbon layer on the surface. The process begins by packing AISI 4340 steel along with charcoal and BaCO3catalyst and heating inside the furnace at 900 oC for 4 hours to facilitate carbon diffusion on the surface. Afterwards, the sample was slowly cooled in the furnace and another sample of base AISI 4340 also prepared. The samples were subsequently examined by using spectrometry test, metallographic observation, hardness test, and wear test. The results show that pack carburized AISI 4340 steel possesses intriguing microstructure which pointed by presence of ferrite and high carbide (Fe3C) phases. The microstructure transformation of pack carburized AISI 4340 steel affects to increase high hardness value (325,4 HV) and high wear resistance compared than the base AISI 4340 steel. Thus, the pack carburized AISI 4340 steel has tenacious capability to attain long wear during mechanical and engineering applications.